Olive's ocean - Henkes, Kevin (New York : Greenwillow Books, 2003)
On a summer visit to her grandmother's cottage by the ocean, twelve-year-old Martha gains perspective on the death of a classmate, on her relationship with her grandmother, on her feelings for an older boy, and on her plans to be a writer.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal starred, August 2003.
Notable/Best Books (A.L.A.), January 2004.
Booklist starred, September 2003.
Horn Book Starred, November 2003.
Keywords: Grandmothers -- Fiction; Family life -- Fiction; Self-perception -- Fiction; Grandmothers -- Fiction; Family life -- Fiction; Self-perception -- Fiction; Grandmothers -- Fiction; Family life -- Fiction; Self-perception -- Fiction; Newbery honor book